Mass spectrometry – an alternative in growth hormone measurement. (September 2014) - Arsene, Cristian G; Kratzsch, Jürgen; Henrion, André
Growth hormone (GH) constitutes a set of closely related protein isoforms. In clinical practice, the disagreement of test results between commercially available ligand-binding assays is still an ongoing issue, and incomplete knowledge about the particular function of the different forms leaves an uncertainty of what should be the appropriate measurand. Mass spectrometry is promising to be a way forward. Not only is it capable of providing SI-traceable reference values for the calibration of current GH-tests, but it also offers an independent approach to highly reliable mass-selective quantification of individual GH-isoforms. This capability may add to reliability in doping control too. The article points out why and how.